2019
DOI: 10.18861/ic.2019.14.2.2918
|View full text |Cite
|
Sign up to set email alerts
|

Midiatização da política, entretenimento e cultura pop. Dimensões conceituais e práticas

Abstract: <p>El artículo describe tres dimensiones de la mediatización de la política, centrando la atención en la relación entre entretenimiento y democracia. En tal sentido, de la investigación bibliográfica realizada, ilustrada por casos particulares, se indican los siguientes aspectos del<br />proceso: (a) la aproximación de la política, en sociedades democráticas, con formas de entretenimiento; (b) la politización del entretenimiento y la cultura pop, transformada en espacios para la discusión d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In this paper, we intend to discuss these approximations between politics and pop culture in the Global South (Martino & Marques, 2022) from theoretical contributions that help to understand the phenomenon of Social TV in Brazil (Canatta, 2019) and even Fan Cultures (Author et al, 2021;Gunderman, 2020;Bennet, 2012 and others) that emerged around this set of profiles on Twitter. So, we conducted an exploratory research based on a Boolean search with some terms found on Twitter during CPI's exhibition.…”
Section: Fan Practices Around the "Cpi Da Covid": Intersections Betwe...mentioning
confidence: 99%
“…In this paper, we intend to discuss these approximations between politics and pop culture in the Global South (Martino & Marques, 2022) from theoretical contributions that help to understand the phenomenon of Social TV in Brazil (Canatta, 2019) and even Fan Cultures (Author et al, 2021;Gunderman, 2020;Bennet, 2012 and others) that emerged around this set of profiles on Twitter. So, we conducted an exploratory research based on a Boolean search with some terms found on Twitter during CPI's exhibition.…”
Section: Fan Practices Around the "Cpi Da Covid": Intersections Betwe...mentioning
confidence: 99%
“…Researchers like Sodré (2004), Braga (2006), Livingstone (2009), Couldry (2008), Couldry and Andreas (2013) and Martino (2019aMartino ( , 2019b, among others, identity a shift in the place of 'the media' in society, and even a transformation in the very concept of 'media'. Roughly, they seem to claim that prior to the 2000s it was possible to locate 'the media' in society: Mainly great broadcast corporations, transmitting to a mass of receivers easily located at their homes, reading printed newspapers, watching their television sets, listening to CDs, and watching and DVD players.…”
Section: The Theoretical Perspective Of Mediatizationmentioning
confidence: 99%